(3GdJTha aj QLGd GdSGOGJ Cgd GdJUhas - (3CHh RjO YHO GdQMef Hf CHj ESeGYjd Hf EHQGgje GdUheYj GdJGOdjs
(3ChdgG (B:s
(3hSejJ gPG GdcJGH GdJTha aj QLGd GdSGOGJ Cgd GdJUha s
(3BNQgG (B:s
(3GdSjO MGL Hf YGeQ Hf LGHQ Hf SYOhf faYfG Gdg Hg HHQcI CeKGdg CLeYjf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B71 - (3U(B87s
(3hGdNW jTjY ajg GdJUMja hGdJMQjas
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B111 ; (3agQSJ GdNRGfI GdYGeI HGdQHGW (B- (3GdLRA (B2 - (3U (B194 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(1103 (3O(B) s
(3JHUQI GdJQGLe(Bs
Keywords: (3GdJGQjNs